Fate and transport processes of phosphorous fractions in selected surface sediments of Cochin Estuary, Southwest Coast of India. Issue 3 (3rd July 2019) - Salas, P. M.; Sujatha, C. H.; Ratheesh Kumar, C. S.; Dayala, V. T.
Abstract: Sediment samples were collected from nine stations located along the Cochin estuary through five seasonal sampling campaigns for evaluating the distribution, accumulation and biogeochemical factors governing the concentration of various phosphorous fractions. Concentrations of sedimentary phosphorus fractions followed the order: iron-bound phosphorus > calcium bound inorganic phosphorous > alkali soluble organic phosphorus > acid soluble organic phosphorous > residual organic phosphorus. The enrichment of calcium bound inorganic phosphorous in the estuarine stations was found to exist in the high alkaline pH. Correlation study revealed that texture of the sediment controlled the distribution of iron bound phosphorous in the sediments. Terrestrial runoff carried huge quantities of humic substances to the riverine sediments that resulted in the peak concentration of alkali bound phosphorous at station S9 during monsoon. Increased levels of acid soluble organic phosphorous was recorded at stations with higher salinity (S5 to S8). Majority of the stations exhibited depleted levels of residual organic phosphorus due to the mineralization process. Meanwhile, total phosphorous ranged between 222.92 ± 3.89 µg/g and 4348.66 ± 15.35 µg/g with significant spatio-temporal variability ( p < 0.01). Besides river run off resulted in the transport of organic matter derived from terrigenous, industrial, agricultural and aquaculture sources which brought about large scale accumulation of recalcitrant organic phosphorous in the sediments. Silt and clay exhibited remarkable positive correlations with iron-bound phosphorus, calcium bound inorganic phosphorous and alkali soluble organic phosphorus indicating the role of fine grained sediments in their dispersal mechanism. Multivariate statistical analysis revealed that distribution of phosphorous fractions were mainly controlled by salinity, granulometry, adsorption, desorption, precipitation, redox status, and the microbial processes occurring in the sedimentary environment.